Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Dan Whitehurst doing gag jokes as Shecky Greene; holding small cigar, wearing open shirt with golden medallions In background: emcee Judge James Ardaiz, and TorNino's manager ?